Robust Trend Analysis in Predicting Histamine Provocation Concentration - Krusińska, E.; Liebhart, J.; Woźniak, M. (Methods of Information in Medicine, 1991)
Trend analysis is used to predict the histamine provocation concentration PC20 during the so-called challenge test, where increasing doses of the bronchoconstricting agent are given to a patient and the spirometric examination is subsequently performed. Classical least-squares analysis of trends as well as least absolute deviations analysis are compared. The results are interesting and promising from a statistical as well as medical point of view. The methods presented can be applied to many practical problems in medicine.
Keywords: Histamine Test; L1-estimation; Prediction; Provocation Concentration PC20; Trend Analysis